The Interplay of IL-21 and BAFF in the Formation and Maintenance of Human B Cell Memory - Karnell, Jodi; Ettinger, Rachel (Frontiers in Immunology, 2012)
To date, IL-21 stands out as the most influential cytokine for human B cell activation and differentiation. Indeed, when compared to other important B cell-tropic cytokines such as IL-2, IL-4, IL-6 and IL-10, IL-21 is clearly the most potent in terms of its ability to influence humoral immune responses in humans. IL-21 has wide reaching actions in determining how B cells will respond to co-stimulation ranging from induction of cell death upon BCR cross-linking to potent induction of class switch recombination and plasma cell differentiation when CD40 molecules are co-engaged. Another crucial B cell factor, exemplified in recent clinical trials, is BAFF/BLys. BAFF plays a critical role in the survival of human B cells and plasma blasts and influences B cell expansion and migration. Recent evidence has shown that IL-21 and BAFF can work in concert to promote and perhaps maintain humoral immunity in humans. Notably, BAFF has the unique ability to substitute for CD40L activities in regard to IL-21-costimulation and differentiation of a specific B cell subpopulation located in the human splenic marginal zone. However, and perhaps surprisingly, BAFF signals do not have the capability to override IL-21-driven cell death events when BCR is engaged. In stark contrast, anti-CD40 ligation of B cells co-activated with IL-21 and anti-IgM not only reverses this aforementioned activation-induced cell death, but transforms this death signal into one that drives plasma cell differentiation. Here we will discuss these two critical B cell factors, IL-21 and BAFF, and their distinct and complimentary effects on human B cell responses.